Translation and validation of the Chinese version of the MD Anderson symptom inventory for measuring perioperative symptom burden in patients with gynecologic cancer - Ting Zhang; Ying-ying Zheng; Zhi-rong Yang; Qiuling Shi; Xin Shelley Wang; Jun Zhao; Min Yang; Chun-lin Wu; Guo-rong Wang (BMC, 2021)
Abstract Background Gynecologic cancers are among the most prevalent malignancies in China. Cervical and uterine cancer respectively account for the sixth and eighth highest incidence of cancer among Chinese women. Abdominal surgery is one of the important treatment methods for gynecological tumors. However, the tumor- and surgery-related symptom burden are not well studied owing to a lack of a standardized and validated assessment tool in the Chinese population. The study aimed to translate and validate the MD Anderson Symptom Inventory for measuring perioperative symptom burden in gynecologic cancer patients (MDASI-PeriOp-GYN) and examine the utility of the Chinese version of MDASI-PeriOp-GYN. Methods The MDASI-PeriOp-GYN was translated in a stepwise manner. First, two native speakers independently translated the 9 PeriOp-GYN symptom items. Then the nine items were translated back into English by two different bilingual translators. After discussion and revision, the four translators reached an agreement. Finally, the finalized Chinese version was administered to women with three common gynecologic cancer types (cervical, ovarian, and endometrial cancers) recruited from the gynecological oncology department of Sichuan Cancer Hospital & Institute between July and October 2019. The reliability and validity of the translated version were assessed. Results Overall, 324 women with gynecologic cancers were enrolled. Cronbach's α values were 0.826 and 0.735 for the symptom severity and interference scales, respectively. Test-retest reliability values were 0.885, 0.873, and 0.914 for symptom severity, PeriOp-GYN, and interference scales. Significant correlations were found between the MDASI-PeriOp-GYN-C and EORTC QLQ-C30 along with the QLQ-OV28 module (− 0.608-0.871, P < 0.001). Known-group validity was supported by significant differences in the scores of the four scales grouped by time intervals, surgery type, and functional status (all P < 0.01). Conclusions The MDASI-PeriOp-GYN-C is a valid and reliable tool for measuring symptoms in Chinese patients undergoing surgery for gynecologic cancers. The tool could be used in clinical practice and clinical trials to instantly gather patients' health and quality of life data.